A checklist of bat-associated macronyssid mites (Acari: Gamasina: Macronyssidae) of Russia, with new host and geographical records - Orlova, M.v.; Klimov, P.b.; Orlov, O.l.; Smirnov, D.g.; Zhigalin, A.v.; Budaeva, I.v.; Emelyanova, A.a.; Anisimov, N.v. (Zootaxa, 2021)
The family Macronyssidae (Acari: Mesostigmata) comprises mostly obligate blood-sucking ectoparasites of bats (Mammalia: Chiroptera) and some other animals, such as small mammals, reptiles and birds. Here, we document and curate previously known data, and, based on our extensive survey, provide this article of bat-associated macronyssid mites of the Russian Federation. We record a total of 24 mite species belonging to 4 genera (Ichoronyssus, Macronyssus, Steatonyssus, and Cryptonyssus). Twenty-seven new host-parasite associations are reported. In addition, were provide data on five major Russian regions, for which bat-associated mite records were lacking.